Analysis of Internal and External Determinant Variables towards Profitability of Islamic Banking in Indonesia (2014-2020) - Febri Ramadhani; Muhammad Rizkan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
Indonesia is a country that adheres to a dual banking system, namely conventional and Islamic Banking. The growth rate of Islamic banking in the last three years is higher than conventional banking. However, in total assets, Islamic banking is still far behind conventional banking. Therefore, it is necessary to study further the performance of Islamic banking reflected in its profitability. So, it becomes an alternative input in determining Islamic banking policies. This study aims to know the factors affecting the profitability (ROA) of Islamic Banking in Indonesia. The data used are the 2014-2020 monthly data in the amount of 79 data. The method used in this study is a Vector Error Correction Model (VECM) to determine the effect of long-run and short-run relationships. The results of the study showed that the long-run relationship of the NPF variable affected and was significant positive toward ROA, CAR affected and was significant negative toward ROA, while the inflation variable had a negative relationship and not significant toward ROA. The results of the short-run relationships showed that the NPF and CAR variables positively affected ROA, while the inflation variable did not significantly affect the ROA.